The direct effect of World Trade Organization law in national legislation (approaches of the People's Republic of China and Russian Federation) - N.E. Tyurina; Li Xu (Ученые записки Казанского университета: Серия Гуманитарные науки)
The principle provision of the Marrakesh Agreement of 1994 providing for harmonization of national laws and regulating external trade relations has been discussed in the paper. Bringing national law in compliance with WTO (World Trade Organization) law does not require, but admits the direct effect of “covered agreements” in the national legal order. Taking into account various approaches to the definition of WTO law in Russian and foreign scientific publications, we have studied it in the context of implementation in national law. The legal acts adopted by the People's Republic of China and Russian Federation according to their obligations under WTO law have been analyzed to identify the specifics of its implementation in these countries. It has been revealed that in both cases the direct effect of WTO law is not a national practice, but the legal backgrounds for that appear to be different. The Chinese and Russian approaches to the direct effect are explained in the related Protocols on accession to the Agreement establishing the WTO supplemented by the Reports of the Working Groups as integral parts. As it follows from these documents, the direct effect in both countries is not entirely rejected, though it may be only a rare and special occasion. The experience of other countries considered in this paper confirms that the direct effect of WTO law is not expected to be a regular practice.